Recruitment and selection process and the impact of Covid-19 - Pomochshikova, Mariya (2021)
This thesis focuses on the current situation in the world, which is directly related to the emerging COVID-19 pandemic, as well as its impact on the HR department of a given company and on the recruitment of employees. The bachelor's thesis describes the system of functioning of the personnel department in a company, human resources, recruitment methods and methods, Eichar metrics, a survey conducted with employees and the COVID-19 pandemic. The practical part is focused on the recruiting process in the MSD company, and its main purpose is to show the recruitment process before the pandemic and indicate the consequences of the pandemic, as well as to conduct research that will help to identify the current changes in the company.